Immunogenicity, efficacy and safety of Nuwiq® (human‐cl rhFVIII) in previously untreated patients with severe haemophilia A—Interim results from the NuProtect Study. Issue 2 (16th August 2017) - Liesner, R. J.; Abashidze, M.; Aleinikova, O.; Altisent, C.; Belletrutti, M. J.; Borel‐Derlon, A.; Carcao, M.; Chambost, H.; Chan, A. K. C.; Dubey, L.; Ducore, J.; Fouzia, N. A.; et al.
Abstract : Introduction: Nuwiq ® (Human‐cl rhFVIII) is a fourth generation recombinant FVIII, produced in a human cell line, without chemical modification or protein fusion. No inhibitors developed in studies with Nuwiq ® in 201 previously treated patients with haemophilia A (HA). The immunogenicity, efficacy and safety of Nuwiq ® in previously untreated patients (PUPs) with severe HA are being assessed in the ongoing NuProtect study. Methods: The study, conducted across 38 centres worldwide, is evaluating 110 true PUPs of all ages and ethnicities enrolled for study up to 100 exposure days (EDs) or 5 years maximum. The primary objective is to assess the immunogenicity of Nuwiq ® (inhibitor activity ≥0.6 BU) using the Nijmegen‐modified Bethesda assay at a central laboratory. Results: Data for 66 PUPs with ≥20 EDs from a preplanned interim analysis were analysed. High‐titre (HT) inhibitors developed in 8 of 66 patients after a median of 11.5 EDs (range 6‐24). Five patients developed low‐titre inhibitors (4 transient). The cumulative incidence (95% confidence interval) was 12.8% (4.5%, 21.2%) for HT inhibitors and 20.8% (10.7%, 31.0%) for all inhibitors. During inhibitor‐free periods, median annualized bleeding rates during prophylaxis were 0 for spontaneous bleeds and 2.40 for all bleeds. Efficacy was rated as "excellent" or "good" in treating 91.8% of bleeds. Efficacy of surgical prophylaxis was "excellent" or "good" for 8 (89%) procedures and "moderate" for 1 (11%). No tolerability concerns were evident. Conclusion: These interim data show a cumulative incidence of 12.8% for HT inhibitors and convincing efficacy and tolerability in PUPs treated with Nuwiq ® .